On the Occurrence of a Haemogregarinae (Apicomplexa) Parasite from Freshwater Turtles of South 24 Parganas, West Bengal, India - Hossen, Molla Sabir; Bandyopadhyay, Probir K; Gürelli, Gözde (Galenos Yayinevi, 2013)
The aim of this study was to investigate Haemogregarine parasites (Apicomplexa: Haemogregarinidae) of freshwater turtles (Lissemys punctata andersoni, Geoclemys hamiltonii) of India.Turtles were collected by net from two ponds of South 24 Parganas, West Bengal, India. A small amount of blood was taken from the subcarapacial vein puncture site. The blood smears were prepared and air dried and fixed in absolute methyl alcohol. The slides were stained with Giemsa.Haemogregarine parasites were recorded from the erythrocytes of turtles. Multiple stages of intraerythrocytic gametocytes (microgametocytes, macrogametocytes, early schizonts and mature schizonts) were observed in blood films.It was found that only twenty out of the twenty five turtles (80%) were infected with the parasite. The prevalence rate was higher in larger turtles in comparison to smaller ones. It was also found that female turtles had a higher prevalence of infection than males.
Keywords: Male; Erythrocytes; Animals; Humans; India; Female; Fresh Water; Apicomplexa; Turtles